Preference of food sellers towards halal labeled fish ball in Kelantan - Zul Ariff Abdul Latiff; Mohammad Amizi Ayob; Mohamad Izwani Halim (2017)
Aim/Purpose The objective of this study is to determine the preferences of food sellers in Kelantan towards the halal-labeled fish ball. Background Fish balls are the popular value-added products in Malaysia. Fish ball production is in second place after fish cracker production for processed fish-based production in Malaysia. Thus, this study tries to expose the preferences of the food sellers toward halal-labeled fish ball based on KAP model. Methodology A convenience sample technique is employed in selecting 58 food sellers in Kelantan. The food sellers were interviewed face-to-face by using a structured questionnaire. Contribution This study is about the perception of the food sellers towards the halal labeled fish ball in Kelantan. Consumers, researchers, society, manufacturers, and government can use the results that had been revealed and the conclusions that had been reached. Findings The result indicates that knowledge, attitude, and practice of food sellers have an impact toward the halal labeled fish ball. This showed that food sellers know the ingredient used in the halal labeled fish ball. The result of factor analysis indicates that knowledge is the major factors that influence the decision of food sellers in selling halal labeled fish ball products. Recommendations for Practitioners Food sellers also should be exposed more about the official halal logo by JAKIM and another country halal logo that is certified by Malaysia government as this can increase their confidence level toward the halal labeled fish ball. The manufacturers should include a halal logo on their fish ball packaging to influence food sellers in purchasing the fish ball. Recommendation for Researchers Another study can be done regarding the consumers’ behavior toward fish ball based on the halal label in Kelantan or Terengganu or Pahang or other states in Malaysia. Impact on Society The results of the study can help manufacturers to understand the needs and wants of customers. Government and local producers need to fulfill the needs of society by producing a fish ball, which has the halal label on the packaging. Future Research This study just focuses on Kelantan, and it does not represent other states. Further study should be done at other state to obtain the nation preference of halal-labeled fish ball